Impact of COVID-19 pandemic on emergency department visits and infant health: a scoping review protocol - Mark Walker; Shi Wu Wen; Yanfang Guo; Romina Fakhraei; Brenden Osborne; Mélika Moorjani-Houle (BMJ Open)
Introduction The novel SARS-CoV-2 pandemic has provided a set of unique challenges for paediatric patients requiring emergency care across the globe. Reduction in paediatric emergency department (ED) usage during the COVID-19 pandemic has been widely reported, but no studies to date have consolidated and described what ramifications these reductions may have on neonatal and infant health. This scoping review aims to characterise the impact of the COVID-19 pandemic on infant ED visits and neonatal and infant health.Methods and analysis A comprehensive literature search will be conducted from March 2020 to July 2022 using the following databases: Embase (Ovid), Web of Science (Clarivate Analytics), Medline (Ovid) and CINAHL (EBSCOhost). This scoping review will use a five-step framework to guide the selection, extraction and analysis of data from eligible studies, with an additional sixth step for clinical consultation. Studies in English reporting the effect of the COVID-19 pandemic on infant ED visits, as well as neonatal and infant health, will be included for screening. Key findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews.Ethics and dissemination Research ethics board approval will not be required due to the nature of the study design. The results of this scoping review will be disseminated through publication in a peer-reviewed journal and presentation at academic conferences.